2014
DOI: 10.1097/shk.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Rather Than Procalcitonin or C-Reactive Protein Predicts Mortality in Patients With Infection

Abstract: Serum cholesterol procalcitonin (PCT) and C-reactive protein (CRP) levels were measured consecutively in 76 critically ill patients at admission to the intensive care unit. The presence of infection was defined according to the CDC (Centers for Disease Control and Prevention) criteria; in-house mortality, underlying diseases, and severity of sepsis were monitored. Nonsurvivors had significantly lower cholesterol levels compared with survivors (69 mg/dL [range, 37-88 mg/dL] vs. 96 mg/dL [range, 71-132 mg/dL], P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
0
24
1
2
Order By: Relevance
“…Some results differ from those described by Biller et al [17], but are similar to those obtained by Huang et al [19], Ho et al [20], and Litton et al [21]. The use of different intensive therapy protocols for severe infections, initiating early treatment during the period between the onset of infection and the administration of effective antibacterial therapy, source control, and damage to specific target organs in patients with multiple organ dysfunction may affect mortality and alter the statistical significance of biomarkers.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Some results differ from those described by Biller et al [17], but are similar to those obtained by Huang et al [19], Ho et al [20], and Litton et al [21]. The use of different intensive therapy protocols for severe infections, initiating early treatment during the period between the onset of infection and the administration of effective antibacterial therapy, source control, and damage to specific target organs in patients with multiple organ dysfunction may affect mortality and alter the statistical significance of biomarkers.…”
Section: Discussioncontrasting
confidence: 91%
“…Our results are comparable with the results obtained by a number of authors. Biller et al [17] found that a cholesterol level > 80 mg/dl is associated with a survival AUC of 0.715 in patients with infection, with sensitivity of 72% and specificity of 66%. Kitazawa et al [15] reported that patients with a bloodstream infection and lower cholesterol levels tended to have higher 30 day mortality, with an AUC of 0.66, sensitivity of 100% and specificity of 39%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low cholesterol levels have been associated with an increased risk of sepsis in critically ill as well as surgical patient populations (23,24). Low cholesterol levels have also been associated with poor survival in several patient populations, including the elderly (25) and patients with congestive heart failure (26-28), rheumatoid arthritis (29), and end-stage renal disease (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Mekanisme yang menjelaskan penurunan kadar kolesterol masih belum jelas. 19 Namun demikian, hipokolesterolemia yang berat pada sepsis berhubungan langsung dengan respon fase akut. Infeksi akut dan kronik akibat bakteri, virus dan parasit dapat menyebabkan hipokolesterolemia akibat pengaruh sitokin proinflamasi pada metabolisme lipoprotein.…”
Section: Metodeunclassified